From Greetings to Corruption: Politicians, Political Parties, and Tweeting in India - Bozarth, Lia; Panda, Anmol; Budak, Ceren; Pal, Joyojeet (ICTD 2020, 2020)
We present an in-depth, language-centric, large-scale study of topical discussions on Twitter by 1,711 Indian politicians from 20 competing political parties in a 4-year timespan. We first show that politicians of all parties collectively indulge more in establishing personal branding through low-substance, personality-focused messaging as opposed to broadcasting policy stances. Additionally, compared to the party-in-power, opposition politicians collectively post more complex tweets and demonstrate higher negativity (e.g., using person-based attack hashtags) especially regarding the issue of corruption. Finally, through a contextual examination of the most retweeted messages from two key leaders—the prime minister and the leader of the largest opposition party, we find that there are qualitatively important distinctions between their styles—while the former focuses on positive-themed messaging, the latter employs confrontation and aggressive language with direct attacks on individuals and issues.